Hemochromatosis and Yersiniosis - Paul C Adams; James Gregor (Canadian Journal of Gastroenterology)
Two patients with documented hemochromatosis and systemic infection with Yersinia enterocolitica are described. The first patient presented with Y enterocolitica septicemia and an infected hip prosthesis which led to the diagnosis of hemochromatosis. The second patient was previously treated for Y enterocolitica with antibiotics but did not recover fully until aggressive phlebotomy therapy was started. The simultaneous occurrence of these two uncommon diseases is related to the ability of the yersinia organism to thrive in the presence of large amounts of iron. The association between iron overload and susceptibility to yersinia infection is reviewed within the context of these two cases.